Arrhythmic risk stratification in heart failure mid‐range ejection fraction patients with a non‐invasive guiding to programmed ventricular stimulation two‐step approach. Issue 5 (2nd August 2020) - Arsenos, Petros; Gatzoulis, Konstantinos A.; Doundoulakis, Ioannis; Dilaveris, Polychronis; Antoniou, Christos‐Konstantinos; Stergios, Soulaidopoulos; Sideris, Skevos; Ilias, Sotiropoulos; Tousoulis, Dimitrios
Abstract: Background: Although some post myocardial infarction (post‐MI) and dilated cardiomyopathy (DCM) patients with mid‐range ejection fraction heart failure (HFmrEF/40%‐49%) face an increased risk for arrhythmic sudden cardiac death (SCD), current guidelines do not recommend an implantable cardiac defibrilator (ICD). We risk stratified hospitalized HFmrEF patients for SCD with a combined non‐invasive risk factors (NIRFs) guiding to programmed ventricular stimulation (PVS) two‐step approach. Methods: Forty‐eight patients (male = 83%, age = 64 ± 14 years, LVEF = 45 ± 5%, CAD = 69%, DCM = 31%) underwent a NIRFs screening first‐step with electrocardiogram (ECG), SAECG, Echocardiography and 24‐hour ambulatory ECG (AECG). Thirty‐two patients with presence of one of three NIRFs (SAECG ≥ 2 positive criteria for late potentials, ventricular premature beats ≥ 240/24 hours, and non‐sustained ventricular tachycardia [VT] episode ≥ 1/24 hours) were further investigated with PVS. Patients were classified as either low risk (Group 1, n = 16, NIRFs−), moderate risk (Group 2, n = 18, NIRFs+/PVS−), and high risk (Group 3, n = 14, NIRFs+/PVS+). All in Group 3 received an ICD. Results: After 41 ± 18 months, 9 of 48 patients, experienced the major arrhythmic event (MAE) endpoint (clinical VT/fibrillation = 3, appropriate ICD activation = 6). The endpoint occurred more frequently in Group 3 (7/14, 50%) than in Groups 1 and 2 (2/34, 5.8%). Logistic regression model adjusted for PVS, age, and LVEF revealed that PVS was an independent MAE predictor (OR: 21.152, 95% CI: 2.618‐170.887, P = .004). Kaplan‐Meier curves diverged significantly (log rank, P < .001) while PVS negative predictive value was 94%. Conclusions: In hospitalized HFmrEF post‐MI and DCM patients, a NIRFs guiding to PVS two‐step approach efficiently detected the subgroup at increased risk for MAE. Abstract : We applied a combined non‐invasive risk factors (NIRFs) leading to programmed ventricular stimulation (PVS), a two‐step risk stratification algorithm, to detect the HFmrEF/40‐49% patients at risk for major arrhythmic events.This combined two‐step approach efficiently detected the patients at increased arrhythmic risk.